Counseling on Optimizing Knowledge Sharing at Micro, Small and Medium Enterprises (MSMEs) Sambal Ijo Bang Juna, Pematangsiantar City - Eliza Arshandy; Christine Dewi Nainggolan; Juan Anastasia Putri; Kevin Indajang; Lenny Dermawan Sembiring; Acai Sudirman (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This service activity aims to provide counseling regarding optimizing knowledge sharing at Sambal Ijo Bang Juna MSMEs in Pematangsiantar City. Knowledge sharing is important in developing small and medium businesses, especially in increasing efficiency and productivity. Through this outreach activity, MSME owners and employees can understand how to share knowledge effectively between fellow employees and business partners to create innovation and increase the competitiveness of green chili products. The method used in this activity is a participatory approach through discussion, training, and direct simulation. This counseling focuses on knowledge-sharing strategies, information management, and the application of simple technology that can support the knowledge-sharing process. The results of this activity will likely encourage Sambal Ijo Bang Juna MSMEs to be more adaptive to market changes and utilize their knowledge for product development and improving service quality.